Long‐term experience with intraoperative electron radiation therapy boost in extremity sarcoma. Issue 7 (20th July 2022) - Laughlin, Brady S.; Golafshar, Michael A.; Lin, Keldon; Goulding, Krista; Roesler, Kimberly; Vern‐Gross, Tamara; Seetharam, Mahesh; Zaniletti, Isabella; Ashman, Jonathan B.
Abstract: Background: In patients with extremity soft tissue sarcoma (eSTS), we describe outcomes of preoperative external beam radiation therapy (EBRT), limb‐sparing surgery (LSS), and intraoperative electron radiation therapy (IOERT). Methods: One hundred and eighteen patients with eSTS treated between October 17, 2002 and July 28, 2021 were identified. EBRT was delivered preoperatively followed by LSS and IOERT. Results: The median follow‐up was 24.9 months. The presentation was primary in 102 (94%) patients and recurrent in 6 (6%) patients. Tumor location was lower extremity in 82 (76%) patients and upper extremity in 26 (24%) patients. Stage distribution was as follows: 3 (3%) IA, 24 (22%) IB, 31 (29%) II, 24 (22%) IIIA, and 25 (23%) IIIB. Final surgical margins were negative in 96 (89%) patients. The 5‐year local control, failure‐free survival, and overall survival were 94%, 75%, and 64%, respectively. Univariate analysis identified age >50, lower extremity, and higher grade as significant negative prognostic factors for overall survival. Grade 3 fracture or osteoradionecrosis requiring surgical fixation, neuropathy, and lymphedema occurred in 7 (6%), 1 (1%), and 0 patients, respectively. Conclusions: This study represents one of the largest series using preoperative EBRT, LSS, and IOERT for eSTS, with high local control and a low rate of late severe toxicity.